Implementasi Algoritma Winnowing untuk Deteksi Kemiripan Proposal Skripsi pada Sistem Informasi KP dan Skripsi (SIKPS) STMIK Bandung - Rahayu, Mina Ismu; Hidayatullah, Ardiansyah Putra (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
The Winnowing algorithm is used to identify similar words/sentences (common subsequences) in two or more compared texts. This algorithm converts the text's N-grams into hash values known as fingerprints. This study aims to design and implement a web-based thesis proposal similarity detection system at STMIK Bandung using the Winnowing algorithm. STMIK Bandung provides an online thesis title submission facility through the SIKPS website. However, students often submit identical titles without realizing that these titles have already been submitted. The developed system will assist students in detecting the similarity level of their submitted thesis proposals with existing proposals in the SIKPS website database.